Definition:Partial Derivative/Second Derivative

From ProofWiki
Jump to navigation Jump to search


Let $\map f {x, y}$ be a function of the two independent variables $x$ and $y$.

The second partial derivatives of $f$ with respect to $x$ and $y$ are defined and denoted by:

\((1):\quad\) \(\displaystyle \dfrac {\partial^2 f} {\partial x^2}\) \(=\) \(\displaystyle \map {\dfrac \partial {\partial x} } {\dfrac {\partial f} {\partial x} }\) \(\displaystyle =: \map {f_{1 1} } {x, y}\)
\((2):\quad\) \(\displaystyle \dfrac {\partial^2 f} {\partial y^2}\) \(=\) \(\displaystyle \map {\dfrac \partial {\partial y} } {\dfrac {\partial f} {\partial y} }\) \(\displaystyle =: \map {f_{2 2} } {x, y}\)
\((3):\quad\) \(\displaystyle \quad \dfrac {\partial^2 f} {\partial x \partial y}\) \(=\) \(\displaystyle \map {\dfrac \partial {\partial x} } {\dfrac {\partial f} {\partial y} }\) \(\displaystyle =: \map {f_{2 1} } {x, y}\)
\((4):\quad\) \(\displaystyle \dfrac {\partial^2 f} {\partial y \partial x}\) \(=\) \(\displaystyle \map {\dfrac \partial {\partial y} } {\dfrac {\partial f} {\partial x} }\) \(\displaystyle =: \map {f_{1 2} } {x, y}\)


Example: $u + \ln u = x y$

Let $u + \ln u = x y$ be an implicit function.


$\dfrac {\partial^2 u} {\partial y \partial x} = \dfrac {\partial^2 u} {\partial x \partial y} = \dfrac u {u + 1} + \dfrac {x y u} {\paren {u + 1}^2}$

Also see